2012
DOI: 10.1097/pas.0b013e31825dd4ff
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Atypical Endometrial Hyperplasia Diagnosed on an Endometrial Biopsy

Abstract: The aims of this study were: (1) to review the rate of concurrent endometrial cancer in patients with a preoperative diagnosis of atypical endometrial hyperplasia (AEH); and (2) to determine the features of concurrent endometrial carcinoma and their impact on the subsequent management of AEH. We reviewed a retrospective series of 219 AEHs diagnosed locally in routine practice, over 24 years, and followed by a repeat biopsy or hysterectomy. Another series of 65 cases with a malignant diagnosis on preoperative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 46 publications
5
47
0
2
Order By: Relevance
“…Eddib et al, found out that; the incidence of endometrial cancer in patients undergone hysterectomy after being diagnosed with atypical endometrial hyperplasia was 17% and none of them was observed to have advanced tumour of more than grade 2 or stage 1B [17]. In similar study done by Rakha et al, suggested that patients who undergone hysterectomy due atypical endometrial hyperplasia and diagnosed with endometrial cancer; their tumours are endometrioid in morphology, early staged, low-graded and show good prognosis [18]. Although most of endometrial hyperplasia associated with endometrial cancer have early stage tumours, it may be accompanied by myometrial invasion.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Eddib et al, found out that; the incidence of endometrial cancer in patients undergone hysterectomy after being diagnosed with atypical endometrial hyperplasia was 17% and none of them was observed to have advanced tumour of more than grade 2 or stage 1B [17]. In similar study done by Rakha et al, suggested that patients who undergone hysterectomy due atypical endometrial hyperplasia and diagnosed with endometrial cancer; their tumours are endometrioid in morphology, early staged, low-graded and show good prognosis [18]. Although most of endometrial hyperplasia associated with endometrial cancer have early stage tumours, it may be accompanied by myometrial invasion.…”
Section: Discussionmentioning
confidence: 77%
“…In endometrial carcinoma the relationship between degree of tumourn and its prognosis is well known for many years and atypical hyperplasia associated with endometrial malignancies are usually low graded and are good prognostic tumours [18]. In our study, patients with postoperative diagnosis of endometrial cancer; 8 cases had grade 1, 6 cases had grade 2 and only one case had grade 3 tumours.…”
Section: Discussionmentioning
confidence: 87%
“…When considering management strategies for women who have a biopsy diagnosis of AEH, clinicians and patients should take into account the considerable rate of concurrent carcinoma [12]. Malignant tumors after AEH diagnosis demonstrate features of good prognosis with endometrioid morphology, lower grade, and early stage, although the overall positive predictive value of AEH is expected at 37% to 48% in the current routine practice [13]. …”
Section: Overviewmentioning
confidence: 99%
“…From a clinical point of view, however, this might not be optimal because today patients with endometrial hyperplasia with atypia are usually treated as if they had a malignant diagnosis, i.e. they undergo hysterectomy unless they want to preserve their fertility [21,22]. None of our logistic regression models was constructed to predict hyperplasia with atypia, and therefore, as expected, when we validated them including hyperplasia with atypia in the malignant group, their diagnostic performance deteriorated (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 89%